Effect of Nutritional Habits on Dental Caries in Permanent Dentition among Schoolchildren Aged 10-12 Years: A Zero-Inflated Generalized Poisson Regression Model Approach - Afshin ALMASI; Abbas RAHIMIFOROUSHANI; Mohammad Reza ESHRAGHIAN; Kazem MOHAMMAD; Yahya PASDAR; Mohammad Javad TARRAHI; Abbas MOGHIMBEIGI; Touraj AHMADI JOUYBARI (Tehran University of Medical Sciences, 2016)
Background: The aim of this study was to assess the associations between nutrition and dental caries in permanent dentition among schoolchildren. Methods: A cross-sectional survey was undertaken on 698 schoolchildren aged 10 to 12 yr from a random sample of primary schools in Kermanshah, western Iran, in 2014. The study was based on the data obtained from the questionnaire containing information on nutritional habits and the outcome of decayed/missing/filled teeth (DMFT) index. The association between predictors and dental caries was modeled using the Zero Inflated Generalized Poisson (ZIGP) regression model. Results: Fourteen percent of the children were caries free. The model was shown that in female children, the odds of being in a caries susceptible sub-group was 1.23(95% CI: 1.08-1.51) times more likely than boys (P=0.041). Additionally, mean caries count in children who consumed the fizzy soft beverages and sweet biscuits more than once daily was 1.41(95% CI: 1.19-1.63) and 1.27 (95% CI: 1.18-1.37) times more than children that were in category of less than 3 times a week or never, respectively. Conclusions: Girls were at a higher risk of caries than boys were. Since our study showed that nutritional status may have significant effect on caries in permanent teeth, we recommend that health promotion activities in school should be emphasized on healthful eating practices; especially limiting beverages containing sugar to only occasionally between meals.